Oil Spill Detection And Contingency Planning Using Radar Imagery and GIS - Assilzadeh, Hamid (2002)
Shipping casualties often resulted in serious accidental spills as experienced in the Straits of Malacca in the past decade. Operational remote sensing and geographic information system (GIS) are important tools for oil spill research and development activities. The use of remote sensing and GIS has been making important contributions to environmental monitoring, modeling and management. The combined use of remotely sensed images and GIS data has received considerable interest in recent years to protect human life, and reduce the environmental consequences of both spills and cleanup efforts. It is necessary to identify vulnerable coastal locations before a spill happens, and promptly perform removal actions when an oil spill occurs, so that the protection priorities can be established and clean-up strategies recognized. In this project an oil spill contingency plan has been created for the Straits of Malacca in three steps as follow: (a) SAR data such as RADARSAT has been used to detect and map oil spills pattern on the Malaysian coastal waters. Information on detection, exact position and size of the oil spill can be identified by remote sensing in SAR images and then plotted on maps in GIS and a priority of the combat efforts and means according to the identified coastal sensitive areas can be carried out; (b) environmental sensitivity index (ESI) map; suggested to provide spill response teams with information about shoreline sensitivity and ranking based on vulnerability of the spill area. This map can show resources at risk in the event of an oil or hazardous substance spill; (c) Prediction of oil spill trajectory, using main seasonal surface currents and surface drift produced by winds. Hypothetical spill trajectories have been simulated for each of the potential launch areas across the entrance of the straits of Malacca. These simulations assumed more than hundred spills occurring in each seasons of the year from each launched area. A successful combating operation to a marine oil spill is dependent on a rapid response from the time the oil spill is reported until it has been fully combated. In order to optimize the decision support capability of the surveillance system for oil spill contingency planning, GIS database have been integrated with the detection tool. An automatic oil spill detection tool was established and information on the exact position and size of the oil spill is then visualized in GIS environment. The system offer opportunities for integration of oil drift forecast models by prediction of wind and current influence on the oil spill for risk assessment using EASI program in PCI software.